Numerical Investigation of the Coherent Structures and Sound Properties in Sonic Coaxial Jets (Advances in Applied Mathematics and Mechanics, 2018)
Numerical investigation of the underexpanded sonic coaxial jets is carriedout using large eddy simulation for three typical inner nozzle lip-thicknesses. Variousfundamental mechanisms dictating the flow phenomena including shock structure,shear layer evolution and sound production are investigated. It is found that the innernozzle lip induces a recirculation zone between inner and outer jets, which significantly influences the behaviors of shock structures and shear layers. The sound propertiesof the coaxial jets are further analyzed in detail. As the inner lip-thickness increases,the helical screech mode switches to an axisymmetric one and high-frequencyscreech also occurs with an oscillation frequency of recirculation zone. Based on thetemporal Fourier transform and correlation analysis, the primary sources of low- andhigh-frequency screeches are associated with the downstream shock cells in the jet columnand the secondary shock structures in the outer annular jet, respectively. Theproper orthogonal decomposition analysis reveals that the dominant structures constructedby the most energetic modes shift from the downstream shock cells regionto the upstream secondary shock region as the lip-thickness increases. The results obtainedin this study provide physical insight into the understanding of the mechanismsrelevant to the coherent structures and sound properties in sonic coaxial jets.